Macular edema in Wyburn-Mason syndrome: Resolution with anti-VEGF intravitreal injections. Case report and review of the literature - Nathan Hupin; Thomas Cahill; Antonella Boschi; Alexandra Kozyreff (American Journal of Ophthalmology Case Reports)
Purpose: Macular edema is an infrequent complication of retinal arteriovenous malformations. We present the management of unilateral macular edema with Bevacizumab 1.25mg/0.05mL and Aflibercept 2mg/0.05mL in a 16-year-old child with Wyburn-Mason syndrome. Observations: The patient developed macular edema after 15 years of unremarkable ophthalmological follow-up. After a one-month observation period, a first intravitreal injection of Bevacizumab 1.25mg/0.05mL, the treatment most frequently described in the literature, was found to be insufficient to reduce the macular edema.After the switch to Aflibercept 2.0mg/0.05mL, a significant reduction in macular edema was observed after three monthly intravitreal injections. This effect was prolonged over the 15-month observation follow-up. Conclusions and importance: Aflibercept 2mg/0.05mL may be a safe and effective option to manage macular edema complications in retinal arteriovenous malformations.